ANALISIS KESANTUNAN BERBAHASA SISWA KELAS VII-A SMP NEGERI 1 LUAHAGUNDRE MANIOMOLO TAHUN AJARAN 2022/2023 - Masri Hulu (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
This research is motivated by the use of language that always pays attention to politeness. This research aims to describe language politeness in discussion activities between teachers and class VIII students of SMP Negeri 1 Luahagundre Maniamolo for the 2022/2023 academic year. The data source in this research is a qualitative approach with a descriptive type. The data collection technique in this research was that the researcher recorded video directly while students were discussing. The findings of this research show that conversations between teachers and students during discussions contain: (1) a scale of formality (2) a scale of indecisiveness (3) a scale of camaraderie. It can be concluded that politeness in speaking will determine how a person's relationship is in terms of communicating with other people as interlocutors or speech partners. If good speech does not contain coercion, arrogance and pressure, always prioritizes other people's benefits and does not offend other people's feelings, then the speaker and speech partner will be better at communicating, but if the opposite happens then the speaker and speech partner will be hindered in communication between them. . Based on the research results, it is recommended that when speaking, students should pay attention to who the person they are speaking to and the situation that is taking place, especially class VIII-A of SMP Negeri 1 Luahagundre Maniamolo to maintain polite language so that they are always liked by others.